مطالعہ قرآن کریم برائے طلباء و طالبات کے حوالے سے علم فاؤنڈیشن کی کاوشوں کا جائزہ: A Review of The Ilm Foundation’s Efforts Regarding the Qur’anic Studies for Students - Amat ur Rehman; Dr. Sajila Kousar; Usama Shafiq (Al Manhal Research Journal, 2022)
The Holy Qur’an is the final and ultimate message of Allah. It is the mean of guidance and success in the world and hereafter. Our elevations and decline in this world are associated with the Holy Qur’an. Therefore, we all need to consolidate our association with the Holy Qur’an. We should wholeheartedly believe in it, recite it regularly, understanding its meanings, act upon its teachings and convey its message to others. It is well-known fact that instructions imported at an early age stay firm in the minds and have long lasting effects. Qur’anic studies for students are a well devised and into great efforts to connect our new generation with the Holy Qur’an at an early age in a simple and easy to understand way. Students will become acquainted with the translation and important topics. It will help them to live their lives according to the percept of the Holy Qur’an. "The Ilm Foundation" is a philanthropic organization, whose objective is to provide a supportive and effective platform to schools of Pakistan from the first to twelfth standard level who are willing to provide modern education with the enhancement of moral values and integrity.